The Implicit Nature of the Anti-Fat Bias - Schupp, Harald T.; Renner, Britta (Frontiers in Human Neuroscience, 2011)
The stigmatization and discrimination of obese persons is pervasive in almost any domain of living. At the explicit level, obese people are associated with a wide range of negative characteristics. Furthermore, research with the implicit association test revealed the implicit nature of the anti-fat bias. Building upon these findings, the present study used event-related brain potential recordings in order to assess key features of implicit processes. Participants viewed a series of schematic portrayals of anorexic, medium, and obese body shapes and tools. In a passive viewing condition, participants were asked to simply look at the stimuli and, in a distraction condition, participants were asked to detect a specific tool. Viewing obese body images, as compared to medium or anorexic body images, elicited a positive potential shift over fronto-central sites and a relative negative potential over occipito-temporal regions in a time window from ~190 – 250 ms. This evaluative brain response to obese body images was similarly pronounced while participants performed a distraction task. Thus, the findings suggest that the anti-fat bias may occur spontaneously, unintentionally, and independent of explicit processing goals. A troublesome picture is emerging in Western cultures suggesting that obese-ism may appear to be as inevitable as a reflex.